A Discussion on of the Limitations and Exceptions of Copyright - Saeed Habiba; zahra Shakeri (Majallah-i ḥuqūq-i taṭbīqī, 2012)
Limitations and Exceptions of Copyright is a main issue in the Intellectual Property Law and it determines national welfare. Limitations and Exceptions strengths the community. Thus, the justice among the owners and the community is essential. This article attempts to study the structure of Copyright and Limitations and Exceptions and provides appropriate recommendations.